REPRODUCTIVE PARAMETERS OF MALE ALBINO RATS AFTER INDUCTION IN SLEEP DEPRIVATION MODELS - Fitranto Arjadi; Ika Murti Harini; Nur Signa Aini Gumilas (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Paradoxical sleep deprivation (PSD) and total sleep deprivation (TSD) cause disrupt of male infertilitybut sleep recovery (SR) can improve male reproduction function that connected with occupational works health. The aim of this study is to determine the difference of reproduction parameters in male albinorats  after exposed by various sleep deprivation models. This research was experimental post-test only with control group design. Rats were divided into 5 groups (6 animals each group) : negativecontrol, PSD (II), TSD (III), PSD with SR, TSD with SR.  The study results  showed that average of spermatogenic  group IV (8.35 ± 0.06) and V (8.27 ± 0.27) had higher scores. group IV had the highest number of Leydig cell (5,91 ± 1,43),  group I had the highest rates (40,02 ± 2,04)   number of Sertoli cell and there were no significant difference  average of epithelial diameter (p=0,598) and height (p=0,895). There were significant difference of spermatogenic score post-SR,  number of Sertoli and Leydig cells, but no significant difference of epithelial diameter and height of seminiferous tubule after exposed by various sleep deprivation stress model. Sleep recovery in occupational work can  repair the histological parameter of reproduction. Key word : male albino rats, reproduction parameters,  sleep deprivation models